Mechanical behavior of dental implants in different positions in the rehabilitation of the anterior maxilla - Corrêa, Cássia Bellotto [UNESP]; Margonar, Rogério [UNESP]; Noritomi, Pedro Yoshito [UNESP]; Vaz, Luis Geraldo [UNESP] (Elsevier, 2014)
Statement of problem In dental rehabilitations that involve implants, the number of implants is sometimes smaller than the number of lost teeth. This fact can affect the biomechanical behavior and success of the implants. Purpose The purpose of this study was to investigate the mechanical behavior of different implant positions in the rehabilitation of the anterior maxilla. Material and methods Three-dimensional models of the maxilla were created based on computed tomography images for 3 different anterior prosthetic rehabilitations. In group IL, the implants were placed in the lateral incisor positions with pontics in the central incisor positions; in group IC, the implants were in the central incisor positions with cantilevers in the lateral incisor positions; and, in group ILIC, one implant was in a lateral incisor position and one was in a central incisor position, with a pontic and a cantilever in the remaining positions. A 150 N load was distributed and applied at the center of the palatal surface of each tooth at a 45-degree angle to the long axis of the tooth. The resulting stress-strain distribution was analyzed for each group. Results The lowest displacement of the prosthetic structure was observed in group IC, although the same group exhibited the largest displacement of the bone tissue. In the bone tissue, the von Mises stress was mainly observed in the cortical bone in all groups. The maximum value of the von Mises stress shown in the cortical tissue was 35 MPa in the implant that neighbors the cantilever in group ILIC. The maximum von Mises stress in the trabecular bone was 3.5 MPa. Conclusion The prosthetic configuration of group IC limited the displacement of the prosthetic structure but led to greater displacement of the bone structure. The use of a cantilever increased the stress concentration in the implant and in the bone structure adjacent to the cantilever under the conditions studied here.